ナンキョク シュウカイ キキュウ (PPB) ニ オケル マルチ ID アルゴスシステム ヲ モチイタ データ デンソウ - 藤井, 良一; フジイ, リョウイチ; 小野, 一彦; オノ, カズヒコ; 太田, 茂雄; オオタ, シゲオ; Fujii, Ryoichi; Ono, Kazuhiko; Ohta, Shigeo (1992)
P(論文) 南極周回気球(PPB)は, 実験期間の大半を昭和基地テレメトリー視野外で飛しょうするため, 通常のテレメトリー方式では, 長時間にわたる観測データを連続的に安定して得ることができない。第32次観測隊から開始されたPPB実験では, マイクロプロセッサーと共に, 一つのアルゴス送信機に複数のID番号を持たせる方式を開発し, 1時間に2kバイト程度のデータを, 飛しょう期間中連続的に安定して得ることができるようになった。本論文では, このマルチIDアルゴスシステムの方式と構成について述べる。 A newly developed multi-ID ARGOS data transfer system for the Polar Patrol Balloon experiment (1990-1993) is described. This system on board the PPBs with a main processor continuously transferred data of about 2kByte/h with great reliability during the entire observation periods (longer than one month). This brief report describes the principle and specifications of the system. departmental bulletin paper